Negative electrode active material for secondary battery, method for producing the same, and secondary battery

By using silicate composite particles with low porosity and high hardness as negative electrode active substances in secondary batteries, the problem of composite particles rupture caused by expansion and contraction of silicon particles is solved, and high capacity and good charge and discharge cycle characteristics are achieved.

CN115004409BActive Publication Date: 2025-02-25PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202080094433.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-01-31
Filing Date
2020-12-17
Publication Date
2025-02-25
Estimated Expiration
2040-12-17

AI Technical Summary

Technical Problem

In the existing secondary batteries, the negative electrode active material containing silicon causes cracking and rupture of the composite particles due to the expansion and contraction of the silicon particles during the charging and discharging process, thereby reducing the charge and discharge cycle characteristics.

Method used

The composite silicate composite particles with a porosity of less than 2% are used as the negative electrode active material. The composite particles are composed of silicon particles and amorphous lithium silicate phase. The lithium silicate phase and the lithium silicate phase are ensured by X-ray diffraction method (XRD) analysis. The peak intensity ratio of silicon particles is below 0.3, and short-term heating and pressurization are performed at high temperatures to enhance the hardness and stability of the particles.

Benefits of technology

By using the improved negative electrode active material, the charge and discharge cycle characteristics of the secondary battery are significantly improved, the irreversible capacity is reduced, and the high capacity and cycle stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115004409B_ABST
    Figure CN115004409B_ABST
Patent Text Reader

Abstract

The negative electrode active material for secondary batteries comprises: silicate composite particles including silicon particles and a lithium silicate phase. Silicon particles are dispersed in the lithium silicate phase, and the porosity of the silicate composite particles is less than 2%. In addition, in a diffraction pattern based on an X-ray diffraction method (XRD), the ratio I2 / I1 of the cumulative intensity I2 of the peak originating from the lithium silicate phase appearing in the range of 2θ=23° to 25° to the cumulative intensity I1 of the peak originating from the Si(111) surface of the silicon particles appearing in the range of 2θ=27° to 30° is less than 0.3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure mainly relates to the improvement of negative electrode active materials for secondary batteries. Background Art

[0002] In recent years, secondary batteries such as non-aqueous electrolyte secondary batteries are expected to be used as power sources for small civilian applications, power storage devices, and electric vehicles due to their high voltage and high energy density. Since the high energy density of the battery is required, it is expected to use materials containing silicon alloyed with lithium as negative electrode active materials with high theoretical capacity density.

[0003] However, since the irreversible capacity of the material containing silicon is large, there is a problem that the initial charge and discharge efficiency (especially the ratio of the initial discharge capacity to the initial charge capacity) is low. Therefore, various technologies have been proposed for pre-introducing lithium equivalent to the irreversible capacity into the material containing silicon. Specifically, a scheme using composite particles containing a lithium silicate phase and silicon particles dispersed in the lithium silicate phase has been proposed (Patent Document 1). The silicon particles contribute to the charge and discharge reaction (reversible storage and release of lithium).

[0004] The composite particles can be produced, for example, by calcining a mixture of glassy lithium silicate powder and silicon particles in a high-temperature and high-pressure atmosphere.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2015-153520 Summary of the invention

[0008] It is known that the above-mentioned composite particles expand and contract to a large extent due to the absorption and release of lithium during charge and discharge. Therefore, as the silicon particles expand and contract, a large stress is generated on the lithium silicate phase present around the silicon particles, thereby causing the composite particles to crack and break. Along with this, the bonding force between the composite particles and the surrounding adhesive materials is weakened, and in particular, the broken composite particles lose the conductive path with the surrounding particles and become isolated. In addition, the side reaction between the electrolyte and the silicon particles is promoted. As a result, the charge and discharge cycle characteristics are reduced.

[0009] In view of the above situation, one scheme of the present disclosure relates to a negative electrode active material for a secondary battery, which comprises: silicate composite particles comprising silicon particles and a lithium silicate phase, the silicon particles being dispersed in the lithium silicate phase, the porosity of the silicate composite particles being less than 2%, and a ratio I2 / I1 of the cumulative intensity I2 of a peak originating from the lithium silicate phase appearing in the range of 2θ=23° to 25° to the cumulative intensity I1 of a peak originating from the Si(111) plane of the silicon particles appearing in the range of 2θ=27° to 30° in a diffraction pattern based on an X-ray diffraction method (XRD) being less than 0.3.

[0010] Another embodiment of the present disclosure relates to a secondary battery comprising: a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode, wherein the negative electrode comprises a current collector and a negative electrode active material layer, and the negative electrode active material layer comprises the negative electrode active material for the secondary battery.

[0011] Another scheme of the present disclosure relates to a method for manufacturing a negative electrode active material for a secondary battery, which comprises the following steps: a step of preparing silicate composite particles having silicon particles and an amorphous lithium silicate phase, in which the silicon particles are dispersed; a step of molding the powder of the silicate composite particles; a step of placing the molded silicate composite particles in a state heated to a temperature of not less than 600° C. and not more than 1000° C. for a period of not less than 40 seconds and not more than 200 seconds; and a step of pressurizing the silicate composite particles in the heated state.

[0012] By using the negative electrode active material disclosed herein, a negative electrode for a secondary battery and a secondary battery having excellent charge and discharge cycle characteristics can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is a cross-sectional view schematically showing a negative electrode active material (LSX particles) for a secondary battery according to one embodiment of the present disclosure.

[0014] Figure 2 This is a schematic perspective view in which a part of a secondary battery according to an embodiment of the present disclosure is cut away.

[0015] Figure 3 This is a schematic diagram showing a schematic configuration of an apparatus used for producing a negative electrode active material for a secondary battery according to an embodiment of the present disclosure.

[0016] Figure 4 This is a diagram showing an example of a diffraction pattern of LSX particles by XRD. DETAILED DESCRIPTION

[0017] The negative electrode active material for a secondary battery according to an embodiment of the present disclosure includes silicate composite particles (hereinafter also referred to as LSX particles) including silicon particles and a lithium silicate phase containing Li, O, and Si. The silicate composite particles have a porosity of 2% or less.

[0018] LSX particles have a sea-island structure in which silicon particles as islands are dispersed in a lithium silicate phase as a sea. High capacity can be achieved by controlling the amount of silicon particles dispersed in the lithium silicate phase, and since silicon particles are dispersed in the lithium silicate phase, the stress caused by the expansion and contraction of silicon particles during charging and discharging can be alleviated by the lithium silicate phase, and the expansion and contraction of LSX particles can be reduced. Therefore, cracking and rupture of LSX particles can be reduced, and it is easy to achieve both high capacity and improved cycle characteristics of the battery.

[0019] In the past, composite particles were manufactured by mixing lithium silicate powder and silicon particles, pulverizing the mixture with a ball mill or the like to form a composite, and calcining the pulverized mixture in a high-temperature and high-pressure atmosphere. Amorphous lithium silicate or crystalline lithium silicate may be used as the lithium silicate powder. However, even when crystalline lithium silicate powder is used, the crystalline lithium silicate may be converted into an amorphous one due to the shear force applied by stirring the mixture. By calcining at a high temperature, the crystallinity of the lithium silicate is restored, and composite particles in which silicon particles are dispersed in the crystalline lithium silicate phase can be obtained.

[0020] However, the higher the crystallinity of the lithium silicate phase, the easier it is to break due to the expansion and contraction of the LSX particles during charge and discharge. If a break occurs, the side reaction with the electrolyte is sometimes increased due to the generation of a new surface. In addition, sometimes the silicon particles are isolated due to the break and become unhelpful for charge and discharge. As a result, the charge and discharge cycle characteristics can be reduced. From this point of view, the lithium silicate phase is preferably low in crystallinity, and the lithium silicate phase can be amorphous.

[0021] For example, in the above-mentioned conventional method, if the calcination step of the composite mixture after pulverization is omitted, LSX particles in which silicon particles are dispersed in a lithium silicate phase with low crystallinity (amorphous) can be obtained. In this case, since the lithium silicate phase is amorphous, the expansion and contraction of the LSX particles are suppressed. However, if the calcination is not sufficient, although the crystallinity of the lithium silicate phase can be reduced, the porosity inside the LSX particles tends to increase. As a result, the surface area that reacts with the electrolyte becomes larger, and side reactions tend to increase. As a result, it is sometimes difficult to obtain low charge and discharge cycle characteristics.

[0022] In contrast, in the present embodiment, for example, a relatively short time (for example, 40 seconds to 200 seconds) of heat treatment is performed at a high temperature (for example, 600° C. to 1000° C.), and the heated mixture is pressurized, so that a calcined body with low porosity and high hardness can be obtained while suppressing the crystallization of the lithium silicate phase. Thus, cracking and rupture of the LSX particles caused by charging and discharging can be suppressed. In addition, the porosity of the LSX particles is less than 2%, which also suppresses the surface area of ​​the LSX particles. Therefore, the reduction in cycle characteristics is suppressed and side reactions will not increase. The pressurization treatment can be performed simultaneously with the heat treatment, or the pressurization treatment can be performed while maintaining the high temperature after heating.

[0023] The porosity (%) of LSX particles can be 1.7% or less, and can be 0.6% or less. Here, "porosity" refers to the ratio of the area occupied by pores in the particle cross section to the total area of ​​the parent particle, which can be obtained by SEM observation of the particle cross section. The specific method for measuring porosity is as follows.

[0024] (1) Using an ion milling device (ex. IM4000) manufactured by Hitachi High-Tech Corporation, a cross section of a mother particle is exposed.

[0025] (2) The exposed particle cross section was observed using SEM, the ratio of the pore area to the total particle cross section area was measured, and the porosity was calculated (pore area x 100 / total particle cross section area). The porosity was the average value of 10 particles.

[0026] The BET specific surface area of ​​LSX particles is, for example, 0.8 m 2 / g or less. The smaller the BET specific surface area, the more the side reactions can be reduced. It should be noted that, for the BET specific surface area, the negative electrode is taken out from the battery in the discharged state by the method described later, and the LSX particles separated from the negative electrode active material layer are measured based on the BET method. The BET method is an analytical method in which an inert gas of known size is adsorbed on the surface of a measurement sample, and the surface area is calculated from the adsorption amount and the area occupied by the inert gas. Nitrogen is used as the inert gas.

[0027] The Vickers hardness of the LSX particles is, for example, 800 HV or more. The greater the Vickers hardness, the higher the hardness, and the more the cracking and breaking of the LSX particles caused by charging and discharging are suppressed. It should be noted that for the Vickers hardness, a sample is prepared by burying the LSX particles separated from the negative electrode active material layer by the method described later in a resin and then grinding, and the Vickers hardness is calculated from the test force and the indentation depth when the indenter on the triangular pyramid is used for pressure application.

[0028] The LSX particles contain a large amount of amorphous lithium silicate phase, so that the charge capacity in the initial charge and discharge tends to increase. Furthermore, the amorphous lithium silicate phase is highly flexible and can easily follow the expansion and contraction of silicon, and the frequency of silicon particles being isolated and unable to be charged and discharged is reduced. As a result, the capacity reduction in the first and subsequent charge and discharge cycles is significantly reduced. Therefore, considering multiple charge and discharge cycles, the LSX particles of this embodiment are advantageous.

[0029] LSX particles may also contain a crystalline silicon oxide phase. LSX particles are manufactured by crushing and compounding silicon and lithium silicate. At this time, in the manufacturing process of lithium silicate, if the silicon raw material is too much relative to the lithium raw material, silicon oxide may be generated. Although most of the silicon oxide becomes amorphous in the crushing process, the crystallized silicon oxide may be finely precipitated in the lithium silicate phase in the subsequent heating process. Crystallized silicon oxide is stable and will not react with lithium ions during charging to become an irreversible reaction. It is also fine and therefore is not easy to hinder the expansion and contraction of silicon particles.

[0030] On the other hand, if the LSX particles have more crystals of lithium silicate such as Li2Si2O5, the particles are easily broken due to expansion and contraction. In addition, the silicate phase is softer than the crystal because it is amorphous, so it is easy to follow the expansion and contraction of silicon particles. Therefore, by sandwiching the two phases of crystalline silicon oxide phase and amorphous lithium silicate phase, the stress accompanying the expansion and contraction of silicon particles can be further alleviated. Thus, a negative electrode active material with good cycle characteristics and small irreversible capacity can be achieved.

[0031] The silicon oxide phase may exist in the LSX particles in a dispersed manner in the lithium silicate phase. That is, the silicon oxide phase and the silicon particles may exist in a dispersed manner in the amorphous lithium silicate phase.

[0032] In the diffraction pattern of the LSX particles of this embodiment based on the X-ray diffraction method (XRD), peaks originating from silicon particles and lithium silicate phases may appear. However, since a large amount of amorphous lithium silicate phase is included, the peak intensity originating from the lithium silicate phase is smaller than before. Specifically, a peak (peak position) originating from the Si (111) surface of the silicon particles may appear in the range of 2θ = 27° to 30°. In addition, a peak (peak position) originating from the lithium silicate phase (Li2Si2O5) may appear in the range of 2θ = 23° to 25°. The peak originating from the Si (111) surface of the silicon particles is separated from the XRD diffraction pattern, and the cumulative intensity of the separated peaks accumulated in the range of 2θ = 23° to 30° is taken as I1. Similarly, the peak originating from the lithium silicate phase is separated from the XRD diffraction pattern, and the cumulative intensity of the separated peaks accumulated in the range of 2θ = 23° to 30° is taken as I2. It should be noted that when multiple peaks appear within the range, the total of the integrated intensities of the respective peaks is calculated. I2 / I1 is 0.3 or less. I2 / I1 may be 0.2 or less, or 0.1 or less. It should be noted that the X-ray used in the XRD method uses Cu Kα rays.

[0033] Figure 4 Examples of XRD diffraction patterns of the LSX particles of the present embodiment and conventional LSX particles are shown. Figure 4 In FIG. 1 , the diffraction pattern of the LSX particle X1 indicated by the solid line relates to the LSX particle of the present embodiment, and the diffraction pattern of the LSX particle Y1 indicated by the dotted line relates to the LSX particle of the conventional example.

[0034] LSX particles X1 and Y1 both have a peak position of a peak originating from the Si(111) plane of silicon particles near 2θ=28°. In addition, there are peak positions of multiple peaks originating from the lithium silicate phase (Li2Si2O5) in the range of 2θ=23° to 25°. In addition, a peak originating from the SiO2(011) plane of the silicon oxide phase was observed near 2θ=26°. In addition, a peak originating from lithium silicate Li2SiO3 was observed near 2θ=19°, and a peak originating from SiO2 was observed in the range of 2θ=20° to 21°.

[0035] However, if the LSX particles X1 and Y1 are compared, the cumulative intensity I2 of the peak derived from the lithium silicate phase in the LSX particle X1 is smaller than the cumulative intensity I1 in the LSX particle Y1.

[0036] In LSX particles, the lithium silicate phase comprises, for example, the formula: Li 2z SiO 2+z The oxide phase is represented by (0<z<1). From the viewpoints of stability, ease of production, lithium ion conductivity, etc., z=1 / 2 is preferred.

[0037] The lithium silicate phase may contain elements other than Li, Si, and O (oxygen). For example, the lithium silicate phase may contain at least one element selected from the group consisting of alkali metal elements (except Li) and Group II elements.

[0038] By including alkali metal elements other than Li in the lithium silicate phase, it is difficult to crystallize, the viscosity in the softened state is low, and the fluidity becomes high. Therefore, even in the heat treatment at a low temperature, it is easy to fill the gaps between silicon particles and to generate dense composite particles. Since the alkali metal elements are cheap, they can be Na and / or K. The atomic ratio of the alkali element X (for example, K) other than Li contained in the lithium silicate phase relative to Li: X / Li can be, for example, 0.1 to 7.1, can be greater than 0.4 and less than 5, and can be greater than 0.7 and less than 2.

[0039] The lithium silicate phase may contain a Group II element. Generally, the silicate phase exhibits alkalinity, but the Group II element has the effect of inhibiting the dissolution of alkali metals from the silicate phase. Therefore, the viscosity of the slurry is easily stabilized when preparing a slurry containing a negative electrode active material. Therefore, the necessity of treatment (such as acid treatment) for neutralizing the alkaline component of the LSX particles is also reduced.

[0040] As the Group II element, at least one selected from the group consisting of Be, Mg, Ca, Sr, Ba and Ra can be used. Among them, Ca is preferred from the perspective of improving the Vickers hardness of the lithium silicate phase and further improving the cycle characteristics. The content of the Group II element relative to the total amount of elements other than O contained in the lithium silicate phase is, for example, 20 mol% or less, 15 mol% or less, or 10 mol% or less.

[0041] The lithium silicate phase may also contain other elements M in addition to alkali metal elements and Group II elements. The element M may be at least one selected from the group consisting of B, Al, Zr, Nb, Ta, La, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W. Specifically, for example, B has a low melting point and is advantageous in improving fluidity during calcination. Although Ca reduces ion conduction, it has the effect of increasing the hardness of the lithium silicate phase. Al, Zr, Nb, Ta and La can increase hardness while maintaining ion conductivity. The content of the element M relative to the total amount of elements other than O contained in the lithium silicate phase is, for example, less than 10 mol%, and can be less than 5 mol%.

[0042] The contents of B, Na, K and Al contained in the lithium silicate phase were determined by quantitative analysis in accordance with JIS R3105 (1995) (analysis method of borosilicate glass), and the content of Ca was determined by quantitative analysis in accordance with JIS R3101 (1995) (analysis method of soda-lime glass).

[0043] The other contained elements are obtained by the following method. First, a sample of the lithium silicate phase or LSX particles containing the lithium silicate phase is completely dissolved in a heated acid solution (a mixed acid of hydrofluoric acid, nitric acid and sulfuric acid), and the carbon in the solution residue is filtered and removed. Then, the obtained filtrate is analyzed by inductively coupled plasma emission spectrometry (ICP-AES) to measure the spectral intensity of each element. Next, a calibration curve is prepared using a commercially available standard solution of the element, and the content of each element contained in the lithium silicate phase is calculated.

[0044] There are lithium silicate phases, silicon oxide phases and silicon particles in the silicate composite particles, which can be distinguished and quantified by using Si-NMR. As described above, the Si content obtained by ICP-AES is the sum of the amount of Si constituting the silicon particles, the amount of Si in the lithium silicate phase and the amount of Si in the silicon oxide phase. On the other hand, the amount of Si constituting the silicon particles can be quantified separately using Si-NMR. Therefore, the amount of Si constituting the silicon particles and the amount of Si in the silicon oxide phase are subtracted from the Si content obtained by ICP-AES, thereby quantifying the amount of Si in the lithium silicate phase. It should be noted that the standard substance required for quantification can be a mixture of a silicate phase and silicon particles containing a known Si content in a specified ratio.

[0045] Desirable Si-NMR measurement conditions are shown below.

[0046] <Si-NMR measurement conditions>

[0047] Measuring device: Varian, solid-state nuclear magnetic resonance spectrometer (INOVA-400)

[0048] Probe: Varian 7mm CPMAS-2

[0049] MAS: 4.2kHz

[0050] MAS speed: 4kHz

[0051] Pulse: DD (45° pulse + signal capture time 1H decoupling)

[0052] Repeat time: 1200 seconds to 3000 seconds

[0053] Observation width: 100kHz

[0054] Observation center: around -100ppm

[0055] Signal capture time: 0.05 seconds

[0056] Cumulative number of times: 560

[0057] Sample volume: 207.6 mg

[0058] In order to improve high capacity and cycle characteristics, the content of silicon particles in LSX particles can be, for example, 30% by mass or more and 80% by mass or less. By setting the content of silicon particles to 30% by mass or more, the proportion of lithium silicate phase becomes smaller, and the initial charge and discharge efficiency is easily improved. By setting the content of silicon particles to 80% by mass or less, the degree of expansion and contraction of LSX particles during charge and discharge is easily reduced. The content of silicon particles in LSX particles is preferably 40% by mass or more, and more preferably 50% by mass or more.

[0059] The silicon particles dispersed in the lithium silicate phase have a granular phase of silicon (Si) single substance, which is composed of a single or multiple crystallites. The crystallite size of the silicon particles is preferably less than 30nm. When the crystallite size of the silicon particles is less than 30nm, the volume change caused by the expansion and contraction of the silicon particles caused by charging and discharging can be reduced, and the cycle characteristics can be further improved. For example, the isolation of the particles caused by the reduction of contact points with the particles when the silicon particles shrink is suppressed due to the formation of pores around the silicon particles, and the reduction of the charge and discharge efficiency caused by the isolation of the particles is suppressed. The lower limit of the crystallite size of the silicon particles is not particularly limited, for example, it is 5nm.

[0060] The crystallite size of the silicon particles is more preferably 2 nm or more and 30 nm or less, and more preferably 2 nm or more and 20 nm or less. When the crystallite size of the silicon particles is less than 20 nm, the expansion and contraction of the silicon particles can be uniformized, and the fine cracks of the particles caused by the expansion and contraction of the silicon particles caused by the charge and discharge can be reduced, thereby improving the cycle characteristics. The crystallite size of the silicon particles is calculated by the half-value width of the diffraction peak attributable to the Si (111) surface of the X-ray diffraction (XRD) pattern of the silicon particles using the Scherrer formula.

[0061] At least a portion of the surface of the LSX particles may be covered with a conductive material. Since the lithium silicate phase lacks electronic conductivity, the conductivity of the LSX particles is also easily reduced. However, by covering the surface of the mother particle with a conductive material and forming a conductive layer, the conductivity of the LSX particles can be significantly improved. As the conductive material, a carbon material is preferred. The carbon material preferably includes at least one selected from the group consisting of a carbon compound and a carbon-containing substance.

[0062] The thickness of the conductive layer is preferably thin enough not to substantially affect the average particle size of the LSX particles. In view of ensuring conductivity and diffusibility of lithium ions, the thickness of the conductive layer is preferably 1 to 200 nm, more preferably 5 to 100 nm. The thickness of the conductive layer can be measured by cross-sectional observation of the LSX particles using a SEM or TEM (transmission electron microscope).

[0063] As carbon compounds, for example, compounds containing carbon and hydrogen, and compounds containing carbon, hydrogen and oxygen can be listed. As carbon-containing substances, low-crystalline amorphous carbon, high-crystalline graphite, etc. can be used. As amorphous carbon, carbon black, coal, coke, charcoal, activated carbon, etc. can be listed. As graphite, natural graphite, artificial graphite, graphitized mesophase carbon particles, etc. can be listed. Among them, amorphous carbon is preferred due to its low hardness and large buffering effect on silicon particles whose volume changes due to charge and discharge. Amorphous carbon can be easily graphitized carbon (soft carbon) or difficult to graphitize carbon (hard carbon). As carbon black, acetylene black, Ketjen black, etc. can be listed.

[0064] LSX particles can be removed from the battery using the following method. First, disassemble the battery and remove the negative electrode, wash the negative electrode with anhydrous ethyl methyl carbonate or dimethyl carbonate, and remove the electrolyte. Next, peel the negative electrode mixture from the copper foil and crush it in a mortar to obtain a sample powder. Next, dry the sample powder in a dry atmosphere for 1 hour and immerse it in slightly boiling 6M hydrochloric acid for 10 minutes to remove alkali metals such as Na and Li that may be contained in the binder. Next, wash the sample powder with ion exchange water, filter it and dry it at 200°C for 1 hour. Then, heat it to 900°C in an oxygen atmosphere and remove the carbon component, so that only the LSX particles can be separated.

[0065] The cross-sectional observation of LSX particles can be carried out, for example, using the following method. First, the battery is disassembled and the negative electrode is taken out, and a cross-sectional polisher (CP) is used to obtain a cross-sectional view of the negative electrode mixture layer. The cross-sectional view of the negative electrode mixture layer is observed using a scanning electron microscope (SEM). Ten LSX particles with a maximum particle diameter of 5 μm or more are randomly selected from the cross-sectional image of the reflected electron image of the negative electrode mixture layer, and for each LSX particle, an element (e.g., carbon) mapping analysis based on energy dispersive X-rays (EDX) is performed. The area containing the element being the object is calculated using image analysis software. The observation magnification is expected to be 2000 to 20000 times. The measured values ​​of the area containing the specified element of the 10 particles obtained are averaged and obtained.

[0066] It should be noted that, during the charge and discharge process, a coating is formed on the surface of the LSX particles by decomposition of the electrolyte, etc. In addition, as described later, the LSX particles sometimes further have a conductive layer covering the surface of the composite particles. Therefore, in order to exclude thin coatings and conductive layers from the measurement range, the EDX-based mapping analysis is performed on a range 1 μm inside the peripheral edge of the cross section of the LSX particles. By mapping analysis based on EDX, the distribution state of the carbon material inside the LSX particles can also be confirmed. Since it becomes difficult to distinguish between the electrolyte and the decomposition products at the end of the cycle, it is preferred to measure the sample before or at the beginning of the cycle.

[0067] Desirable measurement conditions for cross-sectional SEM-EDX analysis are shown below.

[0068] <SEM-EDX measurement conditions>

[0069] Processing equipment: JEOL, SM-09010 (Cross Section Polisher)

[0070] Processing conditions: Acceleration voltage 6kV

[0071] Current value: 140μA

[0072] Vacuum degree: 1×10 -3 ~2×10 -3 Pa

[0073] Measuring device: Electron microscope SU-70 manufactured by HITACHI

[0074] Accelerating voltage during analysis: 10kV

[0075] Field: Free Mode

[0076] Probe Current Mode: Medium

[0077] Probe Current Range: High

[0078] Anode Ap.: 3

[0079] OBJ Ap.:2

[0080] Analysis area: 1μm square

[0081] Analysis software: EDAX Genesis

[0082] CPS: 20500

[0083] Lsec: 50

[0084] Time constant: 3.2

[0085] In addition, for the quantification of each element in the silicate composite particles contained in the negative electrode active material layer in the discharged state, in addition to SEM-EDX analysis, Auger electron spectroscopy analysis (AES), laser ablation ICP mass spectrometry (LA-ICP-MS), X-ray photoelectron spectroscopy analysis (XPS), etc. can also be performed.

[0086] Next, an example of a method for producing LSX particles is described in detail.

[0087] Process (i)

[0088] The raw materials used for lithium silicate are: a raw material mixture containing a raw material containing Si and a Li raw material in a specified ratio. The raw material mixture may contain the above-mentioned alkali metal elements, Group II elements, and / or element M. The mixture mixed with the above-mentioned raw materials in a specified amount is dissolved, and the melt is thinned by a metal roller to produce lithium silicate. The thinned silicate is then heat-treated in an atmospheric atmosphere at a temperature above the glass transition point and below the melting point to crystallize it. It should be noted that the thinned silicate can also be used without crystallization. In addition, the silicate can also be manufactured by solid phase reaction by sintering at a temperature below the melting point without dissolving the mixture mixed with the specified amount.

[0089] Silicon oxide can be used as the Si raw material. For example, lithium carbonate, lithium oxide, lithium hydroxide, lithium hydride, etc. can be used as the Li raw material. These can be used alone or in combination of two or more. The raw materials of alkali metal elements, Group II elements, and element M can include oxides, hydroxides, carbonate compounds, hydrides, nitrates, sulfates, etc. of each element.

[0090] The Si raw material that has not reacted with the Li raw material may remain in the lithium silicate. The remaining Si raw material is dispersed in the lithium silicate in the form of a silicon oxide phase.

[0091] Step (ii)

[0092] Next, raw material silicon is mixed with lithium silicate to form a composite. For example, composite particles are produced through the following steps (a) to (c).

[0093] Process (a)

[0094] First, raw silicon powder and lithium silicate powder are mixed at a mass ratio of, for example, 20:80 to 95:5. As the raw silicon, coarse silicon particles having an average particle size of about several μm to several tens of μm may be used.

[0095] Process (b)

[0096] Next, a pulverizing device such as a ball mill is used to pulverize and compound the mixture of raw silicon and lithium silicate while granulating the mixture. At this time, an organic solvent may be added to the mixture to perform wet pulverization. A predetermined amount of organic solvent may be added to the pulverizing container at once at the beginning of pulverization, or a predetermined amount of organic solvent may be added to the pulverizing container intermittently in multiple times during the pulverization process. The organic solvent plays a role in preventing the pulverized object from adhering to the inner wall of the pulverizing container.

[0097] As the organic solvent, alcohol, ether, fatty acid, alkane, cycloalkane, silicate, metal alkoxide or the like can be used.

[0098] It should be noted that the raw silicon and lithium silicate may be granulated separately and then mixed. In addition, silicon nanoparticles and amorphous lithium silicate nanoparticles may be prepared without using a pulverizing device and then mixed. The nanoparticles may be prepared using a known method such as a gas phase method (e.g., a plasma method) or a liquid phase method (e.g., a liquid phase reduction method).

[0099] Process (c)

[0100] Next, the mixture is pressurized and calcined in a state where it is heated to 600°C to 1000°C in, for example, an inert gas atmosphere (e.g., an atmosphere of argon, nitrogen, etc.). The heating time can be a short time of less than 200 seconds. Pressurization can be performed simultaneously (or in parallel) with heating, or after heating. Pressurization can be performed while maintaining a high temperature state based on heating. Calcination can be performed using a calcination device such as a hot press that can pressurize in an inert atmosphere. During calcination, the silicate softens and flows in a manner that fills the gaps between the silicon particles. As a result, a dense block-shaped calcined body with a silicate phase as a sea portion and silicon particles as an island portion can be obtained.

[0101] When the obtained calcined body is pulverized, silicate composite particles can be obtained. By appropriately selecting the pulverization conditions, silicate composite particles having a predetermined average particle size can be obtained.

[0102] The pressurization treatment can also be performed by rolling the powder of the mixture formed into a sheet in advance. The rolling is usually performed by passing the sheet of the mixture through the gap between two rotating rollers. By passing the sheet of the mixture through the gap of the heated rollers, the mixture can be heated and pressurized at the same time. The sheet of the mixture can be heated before and / or after passing through the rollers. While the mixture formed into a sheet is rolled and heated, the negative electrode active material (LSX particles) for secondary batteries can be continuously manufactured with high productivity. The pressure applied by rolling is, for example, 200MPa to 600MPa.

[0103] Process (iii)

[0104] Next, at least a portion of the surface of the composite particles can be covered with a conductive material to form a conductive layer. The conductive material is preferably electrochemically stable, and a conductive carbon material is preferred. As a method for covering the surface of the composite particles with a conductive carbon material, examples include: a CVD method using hydrocarbon gases such as acetylene and methane as a raw material, a method of mixing coal tar, petroleum asphalt, phenolic resin, etc. with composite particles, and heating to carbonize them, etc. In addition, carbon black can also be attached to the surface of the composite particles. Covering with the conductive carbon material can be performed, for example, by heating a mixture of the conductive carbon material and the fine particles removed at 700°C to 950°C in an inert atmosphere (for example, an atmosphere of argon, nitrogen, etc.).

[0105] Step (iv)

[0106] A step of washing the composite particles (including the case where the surface has a conductive layer) with an acid may also be performed. For example, by washing the composite particles with an acidic aqueous solution, a trace amount of alkaline components existing on the surface of the composite particles generated when the raw silicon and lithium silicate are combined can be dissolved and removed. As the acidic aqueous solution, an aqueous solution of an inorganic acid such as hydrochloric acid, hydrofluoric acid, sulfuric acid, nitric acid, phosphoric acid, carbonic acid, or an aqueous solution of an organic acid such as citric acid, acetic acid, or the like can be used.

[0107] Figure 1 A cross section of an LSX particle 20 as an example of a negative electrode material is schematically shown.

[0108] The mother particle 23 includes a lithium silicate phase 21 and silicon particles 22 dispersed in the lithium silicate phase 21. The mother particle 23 has a sea-island structure in which fine silicon particles are dispersed in a matrix of the lithium silicate phase 21. The surface of the mother particle 23 is covered with a conductive layer 26, and the LSX particle 20 is formed.

[0109] A silicon oxide phase may be dispersed in the lithium silicate phase 21. The SiO2 content in the mother particle 23 measured by Si-NMR is preferably 30% by mass or less, and more preferably less than 7% by mass, for example.

[0110] The mother particle 23 may contain other components in addition to the lithium silicate phase 21, the silicon particles 22, the silicon oxide phase and the carbon material. For example, from the viewpoint of improving the strength of the mother particle 23, a reinforcing material such as an oxide such as ZrO2 or a carbide may be contained in an amount of less than 10% by weight relative to the mother particle 23.

[0111] The average particle size of the silicon particles 22 is less than 500 nm before the initial charge, preferably less than 200 nm, and more preferably less than 50 nm. By appropriately miniaturizing the silicon particles 22, the volume change during charge and discharge is reduced and the structural stability is improved. In addition, the cycle characteristics are improved by making the expansion and contraction of the silicon particles uniform and suppressing particle breakage. The average particle size of the silicon particles 22 can be measured by observing the cross section of the negative electrode material using SEM or TEM. Specifically, the maximum diameter of any 100 silicon particles 22 is averaged and obtained.

[0112] The secondary battery of the embodiment of the present disclosure comprises: a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode. The negative electrode comprises: a current collector, and a negative electrode active material layer comprising the negative electrode active material for the secondary battery. The negative electrode, positive electrode, electrolyte, and separator of the secondary battery of the embodiment of the present disclosure are described below.

[0113] [negative electrode]

[0114] The negative electrode includes, for example, a negative electrode current collector and a negative electrode mixture layer formed on the surface of the negative electrode current collector and containing a negative electrode active material. The negative electrode mixture layer can be formed by applying a negative electrode slurry in which a negative electrode mixture is dispersed in a dispersion medium to the surface of the negative electrode current collector and drying it. The dried coating film can also be rolled as needed. The negative electrode mixture layer can be formed on one surface of the negative electrode current collector or on both surfaces.

[0115] The negative electrode mixture may contain the negative electrode active material for secondary batteries containing LSX particles as an essential component, and may contain a binder, a conductive agent, a thickener, etc. as optional components. The silicon particles in the LSX particles can absorb a large amount of lithium ions, thus contributing to the high capacity of the negative electrode.

[0116] The negative electrode active material may further include other active material materials that electrochemically absorb and release lithium ions. As other active material materials, for example, carbon-based active materials are preferred. The volume of LSX particles expands and contracts with charging and discharging, so when the ratio of LSX particles in the negative electrode active material increases, poor contact between the negative electrode active material and the negative electrode collector is likely to occur with charging and discharging. On the other hand, by combining LSX particles and carbon-based active materials, it is also possible to achieve excellent cycle characteristics while giving the negative electrode a high capacity of silicon particles. The ratio of LSX particles to the total of LSX particles and carbon-based active materials is, for example, preferably 0.5 to 15% by mass, and more preferably 1 to 5% by mass. As a result, it is easy to take into account both high capacity and improved cycle characteristics.

[0117] As carbon-based active materials, for example, graphite, easily graphitized carbon (soft carbon), and difficultly graphitized carbon (hard carbon) can be exemplified. Among them, graphite having excellent charge and discharge stability and low irreversible capacity is preferred. Graphite refers to a material having a graphite-type crystal structure, for example, including natural graphite, artificial graphite, and graphitized mesophase carbon particles. One carbon-based active material can be used alone, or two or more can be used in combination.

[0118] As the negative electrode current collector, a non-porous conductive substrate (metal foil, etc.) or a porous conductive substrate (mesh, net, punched sheet, etc.) is used. Examples of the material of the negative electrode current collector include stainless steel, nickel, nickel alloy, copper, copper alloy, etc. The thickness of the negative electrode current collector is not particularly limited, but from the perspective of balancing the strength and lightness of the negative electrode, it is preferably 1 to 50 μm, and more preferably 5 to 20 μm.

[0119] Examples of binders include fluororesins, polyolefin resins, polyamide resins, polyimide resins, vinyl resins, styrene-butadiene copolymer rubber (SBR), polyacrylic acid and its derivatives. These may be used alone or in combination of two or more. As conductive agents, examples include carbon black, conductive fibers, carbon fluoride, organic conductive materials, etc. These may be used alone or in combination of two or more. As thickeners, examples include carboxymethyl cellulose (CMC), polyvinyl alcohol, etc. These may be used alone or in combination of two or more.

[0120] Examples of the dispersion medium include water, alcohol, ether, N-methyl-2-pyrrolidone (NMP), and mixed solvents thereof.

[0121] [positive electrode]

[0122] The positive electrode includes, for example, a positive electrode current collector and a positive electrode mixture layer formed on the surface of the positive electrode current collector. The positive electrode mixture layer can be formed by applying a positive electrode slurry in which a positive electrode mixture is dispersed in a dispersion medium to the surface of the positive electrode current collector and drying the positive electrode slurry. The dried coating film can also be rolled as needed. The positive electrode mixture layer can be formed on one surface of the positive electrode current collector or on both surfaces.

[0123] The positive electrode mixture may contain a positive electrode active material as an essential component, and a binder, a conductive agent, etc. as optional components.

[0124] As the positive electrode active material, a lithium composite metal oxide can be used. Examples of the lithium composite metal oxide include Li a CoO2、Li a NiO2、Li a MnO2、Li aCo b Ni 1-b O2、Li a Co b M 1-b O c , Li a Ni 1-b M b O c , Li a Mn2O4、Li a Mn 2- b M b O4, LiMePO4, Li2MePO4F. Here, M is at least one selected from the group consisting of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb and B. Me contains at least a transition element (for example, at least one selected from the group consisting of Mn, Fe, Co, and Ni). Here, 0≤a≤1.2, 0≤b≤0.9, and 2.0≤c≤2.3. It should be noted that the a value representing the molar ratio of lithium is the value immediately after the active material is made, and increases or decreases due to charge and discharge.

[0125] As the binder and the conductive agent, the same substances as those exemplified for the negative electrode can be used. As the conductive agent, graphite such as natural graphite and artificial graphite can also be used.

[0126] The shape and thickness of the positive electrode current collector can be selected from the shape and range of the negative electrode current collector. Examples of the material of the positive electrode current collector include stainless steel, aluminum, aluminum alloy, titanium, and the like.

[0127] [Electrolytes]

[0128] The electrolyte includes a solvent and a lithium salt dissolved in the solvent. The concentration of the lithium salt in the electrolyte is, for example, 0.5 to 2 mol / L. The electrolyte may contain a known additive.

[0129] The solvent uses an aqueous solvent or a non-aqueous solvent. As the non-aqueous solvent, for example, cyclic carbonates, chain carbonates, cyclic carboxylates, etc. are used. As cyclic carbonates, propylene carbonate (PC), ethylene carbonate (EC), etc. can be mentioned. As chain carbonates, diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), etc. can be mentioned. As cyclic carboxylates, γ-butyrolactone (GBL), γ-valerolactone (GVL), etc. can be mentioned. The non-aqueous solvent can be used alone or in combination of two or more.

[0130] As the lithium salt, for example, lithium chlorate salts (LiClO4, LiAlCl4, LiB 10 Cl 10etc.), lithium salts of fluorinated acids (LiPF6, LiBF4, LiSbF6, LiAsF6, LiCF3SO3, LiCF3CO2, etc.), lithium salts of fluorinated imides (LiN(CF3SO2)2, LiN(CF3SO2)(C4F9SO2), LiN(C2F5SO2)2, etc.), lithium halides (LiCl, LiBr, LiI, etc.), etc. The lithium salts may be used alone or in combination of two or more.

[0131] [Separator]

[0132] It is usually desirable to sandwich a separator between the positive electrode and the negative electrode. The separator has high ion permeability and has appropriate mechanical strength and insulation. As the separator, a microporous film, a woven fabric, a non-woven fabric, etc. can be used. As the material of the separator, for example, polyolefins such as polypropylene and polyethylene can be used.

[0133] As an example of the structure of a secondary battery, there can be cited an electrode group in which a positive electrode and a negative electrode are wound with a separator, and an electrolyte is housed in an outer body. Alternatively, instead of a wound electrode group, an electrode group in another form such as a stacked electrode group in which a positive electrode and a negative electrode are stacked with a separator can be used. The secondary battery can be in any form such as a cylindrical, square, coin-shaped, button-shaped, laminated, etc.

[0134] Figure 2 This is a schematic perspective view of a partially cut-away square secondary battery according to an embodiment of the present disclosure.

[0135] The battery comprises: a square battery case 4 with a bottom, an electrode group 1 and an electrolyte housed in the battery case 4, and a sealing plate 5 for sealing the opening of the battery case 4. The electrode group 1 comprises: a thin and long strip-shaped negative electrode, a thin and long strip-shaped positive electrode, and a separator sandwiched therebetween. The negative electrode, the positive electrode, and the separator are wound around a flat winding core, and the winding core is pulled out to form the electrode group 1. The sealing plate 5 comprises: a liquid injection port blocked by a sealing plug 8, and a negative terminal 6 insulated from the sealing plate 5 by a gasket 7.

[0136] One end of the negative electrode lead 3 is attached to the negative electrode collector of the negative electrode by welding or the like. One end of the positive electrode lead 2 is attached to the positive electrode collector of the positive electrode by welding or the like. The other end of the negative electrode lead 3 is electrically connected to the negative electrode terminal 6. The other end of the positive electrode lead 2 is electrically connected to the sealing plate 5. A resin frame is arranged on the upper part of the electrode group 1, which separates the electrode group 1 and the sealing plate 5 and separates the negative electrode lead 3 and the battery case 4.

[0137] The method for producing a negative electrode active material for a secondary battery according to an embodiment of the present disclosure, for example, comprises the following steps: a step of preparing silicate composite particles having silicon particles and an amorphous lithium silicate phase in which silicon particles are dispersed; a step of press-molding the powder of the silicate composite particles; a step of placing the press-molded silicate composite particles in a state heated to 600° C. or higher and 1000° C. or lower for a period of 40 seconds or higher and 200 seconds or lower; and a step of pressurizing the silicate composite particles in a heated state. The step of pressurizing the silicate composite particles may be a step of rolling the silicate composite particles in a heated state. The above steps (i) to (ii) up to (b) correspond to the step of preparing the silicate composite particles.

[0138] Figure 3 Schematic diagram showing a schematic configuration of a production device used for producing a negative electrode active material for a secondary battery according to an embodiment of the present disclosure. The production device 30 includes a transport unit 31 , a pressurizing unit 32 , and a preheating unit 35 .

[0139] The powder of silicate composite particles (LSX particles) is pre-molded into, for example, a sheet shape. The molding process can be performed by, for example, a method of compressing the powder into a sheet shape using a pair of rollers or a method of pressing using a mold. The molded LSX particles are conveyed to the pressurizing unit 32 via the conveying unit 31.

[0140] The conveying section 31 has a function of supplying the molded LSX pellets 36 to the pressurizing section 32. The conveying section 31 may be constituted by, for example, a belt conveyor. As the belt conveyor, a steel belt, a mesh belt, or the like may be used.

[0141] The LSX pellets 36 on the conveying section 31 are heated by the preheating section 35 before being conveyed to the pressurizing section 32. During the heating period, the temperature of the LSX pellets may be maintained at 600° C. or more and 1000° C. or less. In addition, the heating time may be 40 seconds or more and 200 seconds or less. The heating time is the time required for the LSX pellets 36 to pass through the preheating section 35.

[0142] The pressurizing section 32 includes a pair of rollers consisting of an upper roller 33a and a lower roller 33b. The upper roller 33a and the lower roller 33b are provided with heating sections 34a and 34b inside, respectively. As the configuration of the heating sections 34a and 34b, a jacket heater, a ceramic heater, a halogen lamp heater, a carbon heater, a flash lamp heater, an induction heater, etc. can be used. The heating sections 34a and 34b can be provided inside the upper roller 33a and the lower roller 33b, respectively, and / or can also be provided on the outer periphery of the upper roller 33a and the lower roller 33b. The pressure during pressurization is, for example, not less than 200 MPa and not more than 600 MPa, and can be not less than 300 MPa and not more than 500 MPa. By the pressurizing section 32, the LSX particles supplied from the conveying section 31 are pressurized in a heated state, and roasting is performed, and a roasted body 37 can be obtained.

[0143] <Example>

[0144] Hereinafter, the present disclosure will be specifically described based on Examples and Comparative Examples, but the present invention is not limited to the following Examples.

[0145] <Example 1>

[0146] [Preparation of LSX particles]

[0147] Lithium carbonate and silicon dioxide were mixed in a molar ratio of Li2CO3:SiO2=34:66, and the mixture was dissolved at 1500°C for 5 hours in an inert gas atmosphere, and the melt was passed through a metal roller to form a sheet, and then heat-treated at 750°C for 5 hours to obtain a lithium silicate composite oxide in the form of a mixed phase of amorphous and crystalline. The obtained lithium silicate composite oxide was crushed into an average particle size of 10 μm.

[0148] A lithium silicate composite oxide with an average particle size of 10 μm and raw silicon (3N, average particle size of 10 μm) were mixed at a mass ratio of 70:30. The mixture was filled into a pot (SUS, volume: 500 mL) of a planetary ball mill (Fritsch, P-5), 24 SUS balls (diameter 20 mm) were placed and the lid was closed, and the mixture was pulverized at 200 rpm for 25 hours in an inert atmosphere.

[0149] Then, the crushed product was press-formed into a sheet with a thickness of 4.2 mm at room temperature to obtain a sheet-like molded body. Figure 3 In the apparatus shown, a calcined body was obtained. A pressure of 400 MPa was applied to the compact by the pressurizing unit 32. The heating temperature was set to 800° C. The conveying speed was set so that the heating time was 100 seconds.

[0150] Then, the calcined body was crushed, passed through a 40 μm sieve, and mixed with coal tar (MCP250 manufactured by JFE Chemical Corporation), and the mixture was calcined at 800°C for 5 hours in an inert atmosphere to cover the surface of the LSX particles with conductive carbon and form a conductive layer. The covering amount of the conductive layer was 5% by mass relative to the total mass of the LSX particles and the conductive layer. Then, using a sieve, LSX particles with an average particle size of 5 μm having a conductive layer were obtained. XRD analysis was performed on the LSX particles, and peaks derived from Si, SiO2, Li2Si2O5, and Li2SiO3 were measured.

[0151] [Production of negative electrode]

[0152] LSX particles and graphite were mixed at a mass ratio of 5:95 to serve as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), styrene-butadiene rubber (SBR) and lithium polyacrylate were mixed at a mass ratio of 96.5:1:1.5:1, and after adding water, a mixer (manufactured by PRIMIX Corporation, TKHIVIS MIX) was used to stir and prepare the negative electrode slurry. Next, a layer of 100% slurry ... 2 The negative electrode slurry was applied in a manner that the mass of the negative electrode mixture was 190 g, and the coating was dried and then rolled to form a copper foil with a density of 1.5 g / cm 3 The negative electrode of the negative electrode mixture layer.

[0153] [Production of positive electrode]

[0154] Lithium cobalt oxide, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 95:2.5:2.5, N-methyl-2-pyrrolidone (NMP) was added, and then stirred using a mixer (TKHIVIS MIX manufactured by PRIMIX Corporation) to prepare a positive electrode slurry. Next, the positive electrode slurry was applied to the surface of the aluminum foil, and the coating was dried and then rolled to form a 3.6 g / cm2 film on both sides of the aluminum foil. 3 The positive electrode of the positive electrode mixture layer.

[0155] [Preparation of electrolyte]

[0156] A non-aqueous electrolyte was prepared by dissolving LiPF6 at a concentration of 1.0 mol / L in a mixed solvent containing ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7.

[0157] [Manufacturing of Secondary Batteries]

[0158] Tabs were installed on each electrode, and the positive electrode and the negative electrode were spirally wound with the tabs located at the outermost periphery through a separator to produce an electrode group. The electrode group was inserted into an outer body made of an aluminum laminate film, vacuum dried at 105°C for 2 hours, and then injected with a non-aqueous electrolyte, and the opening of the outer body was sealed to obtain a secondary battery A1.

[0159] <Example 2>

[0160] When the molded body is placed Figure 3 When a calcined body was obtained in the apparatus shown, the heating temperature of the molded body was set to 800° C., and the conveying speed was set so that the heating time became 140 seconds.

[0161] Except for the above, LSX particles were prepared in the same manner as in Example 1, and a negative electrode including the LSX particles was produced to obtain a secondary battery A2.

[0162] <Comparative Example 1>

[0163] After the mixture of the lithium silicate composite oxide and the raw silicon was pulverized, the pulverized product was sintered at 600° C. for 5 hours in an inert atmosphere while applying pressure to the mixture by hot pressing, thereby obtaining a calcined body of the mixture.

[0164] Then, the calcined body was crushed, passed through a 40 μm sieve, and mixed with coal tar (MCP250 manufactured by JFE Chemical Corporation), and the mixture was calcined at 800° C. for 5 hours in an inert atmosphere to cover the surface of the LSX particles with conductive carbon and form a conductive layer. The coating amount of the conductive layer was 5% by mass relative to the total mass of the LSX particles and the conductive layer. Then, using a sieve, LSX particles (secondary particles) having an average particle size of 5 μm with a conductive layer were obtained.

[0165] Using the above-mentioned LSX particles, a negative electrode was produced in the same manner as in Example 1 to obtain a secondary battery B1.

[0166] <Comparative Example 2>

[0167] After the mixture of lithium silicate composite oxide and raw silicon was pulverized, the pulverized product was calcined at 700° C. for 2 hours under vacuum while applying pressure to the mixture by discharge plasma calcination to obtain a calcined body of the mixture.

[0168] Then, the calcined body was crushed, passed through a 40 μm sieve, and mixed with coal tar (MCP250 manufactured by JFE Chemical Corporation), and the mixture was calcined at 800° C. for 5 hours in an inert atmosphere to cover the surface of the LSX particles with conductive carbon and form a conductive layer. The coating amount of the conductive layer was 5% by mass relative to the total mass of the LSX particles and the conductive layer. Then, using a sieve, LSX particles with an average particle size of 5 μm having a conductive layer were obtained.

[0169] Using the above-mentioned LSX particles, a negative electrode was produced in the same manner as in Example 1 to obtain a secondary battery B2.

[0170] The following evaluations were performed on each of the batteries of Examples and Comparative Examples.

[0171] [Charge and discharge cycle test]

[0172] For each battery, charge and discharge were repeatedly performed under the following conditions.

[0173] <Charging>

[0174] The battery was charged at 25° C. at a constant current of 1 It (800 mA) until the voltage reached 4.2 V, and then charged at a constant voltage of 4.2 V until the current reached 1 / 20 It (40 mA).

[0175] <Discharge>

[0176] The battery was discharged at a constant current of 1 It (800 mA) at 25°C until the voltage reached 2.75V.

[0177] The pause period between charge and discharge was 10 minutes. The ratio of the discharge capacity at the 500th cycle to the discharge capacity at the 1st cycle was taken as the cycle retention rate.

[0178] The evaluation results of each battery A1, A2, B1 and B2 are shown in Table 1. It should be noted that Table 1 shows the porosity, BET specific surface area, and Vickers hardness of the LSX particles used as the negative electrode active material of each battery. In addition, Table 1 also shows the ratio I2 / I1 of the cumulative intensity I2 of the peak derived from the lithium silicate phase to the cumulative intensity I1 of the peak derived from the Si (111) surface of the silicon particles by XRD analysis of the LSX particles.

[0179] [Table 1]

[0180]

[0181] According to Table 1, compared with battery B1 in which the negative electrode active material uses LSX particles with a porosity greater than 2% and I2 / I1 greater than 0.3, and battery B2 in which the negative electrode active material uses LSX particles with a porosity less than 2% but I2 / I1 greater than 0.3, batteries A1 and A2 in which the negative electrode active material uses LSX particles with a porosity less than 2% and I2 / I1 less than 0.3 can obtain a high cycle maintenance rate.

[0182] Industrial Applicability

[0183] The present disclosure can provide a nonaqueous electrolyte secondary battery with high capacity and good charge-discharge cycle characteristics. The nonaqueous electrolyte secondary battery of the present disclosure is useful as a main power source for mobile communication devices, portable electronic devices, and the like.

[0184] Description of Reference Numerals

[0185] 1 Electrode set

[0186] 2 Positive lead

[0187] 3 Negative lead

[0188] 4 Battery Case

[0189] 5 Sealing plate

[0190] 6 Negative terminal

[0191] 7 Gasket

[0192] 8 Sealing plug

[0193] 20 LSX particles

[0194] 21 Lithium silicate phase

[0195] 22 Silicon particles

[0196] 23 Masterbatch

[0197] 26 Conductive layer

[0198] 30 Manufacturing equipment

[0199] 31 Conveying Department

[0200] 32 Pressurization section

[0201] 33a Upper roller

[0202] 33b Lower roller

[0203] 34a, 34b Heating section

[0204] 35 Preheating unit

Claims

1. A negative electrode active material for a secondary battery, comprising: silicate composite particles containing silicon particles and a lithium silicate phase, The silicon particles are dispersed in the lithium silicate phase, The porosity of the silicate composite particles is less than 2%, In a diffraction pattern based on an X-ray diffraction method (XRD), a ratio I2 / I1 of a cumulative intensity I2 of a peak originating from the lithium silicate phase appearing in a range of 2θ=23° to 25° to a cumulative intensity I1 of a peak originating from the Si(111) plane of the silicon particles appearing in a range of 2θ=27° to 30° is 0.3 or less, The lithium silicate phase contains Li 2z SiO 2+z , where z = 1 / 2.

2. The negative electrode active material for a secondary battery according to claim 1, wherein The BET specific surface area of ​​the silicate composite particles is 0.8 m 2 / g or less.

3. The negative electrode active material for a secondary battery according to claim 1, wherein The Vickers hardness of the silicate composite particles is greater than 800 HV.

4. The negative electrode active material for a secondary battery according to any one of claims 1 to 3, wherein The content of the silicon particles contained in the silicate composite particles is 30% by mass or more.

5. The negative electrode active material for a secondary battery according to any one of claims 1 to 3, wherein The lithium silicate phase includes at least one element selected from the group consisting of alkali metal elements other than Li and Group II elements.

6. The negative electrode active material for a secondary battery according to any one of claims 1 to 3, wherein The lithium silicate phase further comprises an element M, The element M is at least one selected from the group consisting of B, Al, Zr, Nb, Ta, La, V, Y, Ti, P, Bi, Zn, Sn, Pb, Sb, Co, Er, F and W.

7. A secondary battery comprising: a positive electrode, a negative electrode, an electrolyte, and a separator interposed between the positive electrode and the negative electrode, The negative electrode comprises a current collector and a negative electrode active material layer. The negative electrode active material layer contains the negative electrode active material for a secondary battery according to any one of claims 1 to 6.

8. A method for producing a negative electrode active material for a secondary battery according to any one of claims 1 to 6, comprising the following steps: A preparation step: a step of preparing silicate composite particles including silicon particles and an amorphous lithium silicate phase, wherein the silicon particles are dispersed in the lithium silicate phase; The step of molding the silicate composite particle powder; The step of leaving the formed silicate composite particles to stand in a state heated to 600° C. or higher and 1000° C. or lower for a period of 40 seconds or higher and 200 seconds or lower; and and a step of pressurizing the silicate composite particles in the heated state.

9. The method for producing a negative electrode active material for a secondary battery according to claim 8, wherein: The step of pressurizing the silicate composite particles is a step of rolling the silicate composite particles in the heated state.

Citation Information

Patent Citations

  • Powder for negative electrode of lithium ion secondary battery, and method of manufacturing the same

    JP2015153520A

  • Negative electrode active material for nonaqueous electrolyte secondary batteries, and nonaqueous electrolyte secondary battery

    CN106575751A

  • Negative electrode active material for non-aqueous electrolyte secondary batteries, and non-aqueous electrolyte secondary battery

    CN107112534A

  • Nonaqueous electrolytic secondary battery

    JP2013251097A